SEMEN, KYRYLO AND YURII STEFANYKS IN FAMILY EPISTLES - Hrytsiuk, Mariia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
Writers’ correspondence makes a significant and valuable part of literary studies, discovering life and creative portraits of writers and representatives of their families, thus expanding and objectively outlining the research horizons of the Ukrainian literary process. The aim of the proposed article is to partially highlight creative, public and cultural-enlightening activities of Vasyl Stefanyk’s three sons – Semen, Kyrylo and Yurii, written on the basis of the family correspondence of the father and his sons, of three brothers with one another (as well as the correspondence with other relatives, literary, cultural, public and religious activists of that time, friends), of archival materials, works on literary criticism and country studies, recollections; there are examined Vasyl Stefanyk’s letters of different periods, where the author mentions his sons, the image of Stefanyk-father and his sons’ portraits are analysed with the help of biographical, historical and psychological approaches to studying the issue, constituting research methods. As a result, the uniqueness of the epistolary heritage of Vasyl Stefanyk’s family and the peculiarity of relationships and communication of Stefanyk-father and Stefanyks-sons, as well as of the sons with one anotherare demonstrated, the peculiarities of characters and the main life milestones of Semen, Kyrylo and Yurii Stefanyks are revealed (this makes the practical significance and novelty of the presented research), the significance of Stefanyks’ family correspondence in the all-Ukrainian context as well as the necessity and perspective of the research of the literary, public and cultural-enlightening heritage of Semen, Kyrylo and Yurii Stefanyks, in particular, are proved.